2021
DOI: 10.1002/anie.202110311
|View full text |Cite
|
Sign up to set email alerts
|

An on‐surface Diels–Alder reaction

Abstract: The Diels–Alder reaction is one of the most popular reactions in organic chemistry. However, its use in the field of on‐surface synthesis is hampered by the spatial restrictions of this cycloaddition reaction. Herein we selected a cyclic strained triyne to demonstrate an on‐surface hexadehydro‐Diels–Alder reaction in a single molecule. The reaction was studied in detail by means of atomic force microscopy (AFM) with CO‐functionalized tips. Our results pave the way to use this iconic pericyclic reaction for on‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…In the past decade, on‐surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11–25] including graphene nanoribbons, [14, 15] cyclo[18]carbon, [16] and biphenylene sheets [17] . Recently, several cycloaddition reactions have been achieved on surfaces, [26–37] such as azide–alkyne cycloaddition, [26, 27] Diels–Alder reaction, [28–30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho ‐dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, on‐surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11–25] including graphene nanoribbons, [14, 15] cyclo[18]carbon, [16] and biphenylene sheets [17] . Recently, several cycloaddition reactions have been achieved on surfaces, [26–37] such as azide–alkyne cycloaddition, [26, 27] Diels–Alder reaction, [28–30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho ‐dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, on-surface reactions have provided a unique pathway for the atomically precise synthesis of novel nanostructures, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] including graphene nanoribbons, [14,15] cyclo [18]carbon, [16] and biphenylene sheets. [17] Recently, several cycloaddition reactions have been achieved on surfaces, [26][27][28][29][30][31][32][33][34][35][36][37] such as azide-alkyne cycloaddition, [26,27] Diels-Alder reaction, [28][29][30] the [2+2+2] cyclotrimerization of alkynes, [31] the dehalogenative [2+2] [32] and [2+2+2] cycloaddition of ortho-dihalogenated arenes, [33] and the [3+2] cycloaddition of azomethine ylide and cyano, [34] which provide various carbocycles and heterocycles. More recently, Li et al reported the one-step [1+1+1+1] cycloaddition of phenylacetylenes to achieve the synthesis of tetraphenyl- [4]radialenes on Cu(100); [38] this is the only example of the synthesis of radialenes on a surface to date.…”
mentioning
confidence: 99%
“…Die Arbeitsgruppen von Diego Peña an der Universität Santiago de Compostela (Spanien) und Leo Gross bei IBM Research Zürich, haben nun erstmals eine Diels‐Alder‐Reaktion auf einer Oberfläche beobachtet, doch dazu mussten sie auf eine sehr viel kompliziertere Variante der Reaktion zurückgreifen [1]. Statt drei Doppelbindungen im Kreis tanzen zu lassen, benutzten sie drei Dreifachbindungen, also eine Hexa‐Dehydro‐Diels‐Alder‐Reaktion.…”
Section: Abbunclassified
“…In the development of novel low-dimensional organic polymers, extensive theoretical and experimental studies of surface-confined polymerization have been conducted for various monomers [6][7][8][9]11]. Those investigations focused mainly on the coupling of terphenyl derivatives [20][21][22], PAHs (polyaromatic hydrocarbons) [6,7,12,13,23], triazines [24][25][26], and other compounds [27][28][29] on catalytic Ag, Au and Cu surfaces under UHV (ultra-high vacuum) conditions. The results of the cited examples proved that it is possible to control and optimize the self-assembly of the MO intermediates and to tune the properties of the final polymer via smart modification of the intrinsic properties of the monomers at play.…”
Section: Introductionmentioning
confidence: 99%